1992
DOI: 10.1121/1.402622
|View full text |Cite
|
Sign up to set email alerts
|

Particle column formation in a stationary ultrasonic field

Abstract: Acoustic radiation-force theory for noninteracting particles predicts that when a particle suspension is exposed to a stationary ultrasonic field, the particles may become concentrated at half-wavelength intervals. In a plane stationary field, these particle concentrations would have the shape of uniform planar sheets. Gould and Coakley have observed that particles within these sheets often redistribute to form striated columns in the direction of the ultrasonic beam.In this paper, it is shown that particle co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 0 publications
1
61
0
Order By: Relevance
“…It is also assumed that the particle is rigid, which is a good assumption for particles immersed in an air medium. The dimensionless form of U is considered, which is calculated by [15] 2 0…”
Section: A Daf Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also assumed that the particle is rigid, which is a good assumption for particles immersed in an air medium. The dimensionless form of U is considered, which is calculated by [15] 2 0…”
Section: A Daf Simulationmentioning
confidence: 99%
“…These dynamic field technologies can be implemented by several methods. It has been previously demonstrated that one emitter and a reflector can be used to create a standing wave that traps particles in fixed positions in space [15]- [17]. With this technology, it is possible to trap particles and transport them by changing the driving frequency [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…In a standing wave, quartz wind is not observed. 17 Instead, Rayleigh streaming may occur 11 and the driving force is also in this case proportional to a spatial gradient in the (time-averaged) energy density. The mechanism is dissipation of acoustic energy adjacent to a solid wall within a resulting boundary layer.…”
Section: 9mentioning
confidence: 99%
“…to defined locations in suspending media (Dyson et al, 1974;Whitworth and Coakley, 1992;Coakley et al, 1994;Saito et al, 1998;Bazou et al, 2005;Gherardini et al, 2005;Bazou et al, 2006;Garvin et al, 2011). The primary acoustic radiation force generated along the direction of sound propagation is largely responsible for the movement of cells and particles within an ultrasound standing wave field (Gor'kov, 1962;Gol'dberg, 1971;Gould and Coakley, 1974).…”
Section: Figmentioning
confidence: 99%